Relationship between the total quality management mindset of the nursing personnel and the perceived quality of service in Saint Louis Hospital - Chiachuabsilp, Agnes
One management approach found to improve quality of service is Total Quality Management (TQM) which is a method of process improvement for achieving customer satisfaction without the need for substantial increase in resources.This study aimed to assess the TQM mindset of the nursing personnel and identify its relationship to perceived quality of service in St. Louis Hospital (SLH), Thailand, in general and of the Division of Nursing Pastoral Care, in particular. Specifically, the objectives were as follows:1. To determine the TQM mindset of the nursing personnel in St. Louis Hospital through the use of TQM mindset checklist.1.1. To identify the factors that are related to the TQM mindset of the nursing personnel, specifically socio-demographic factors, job-related factors, and organizational factors.1.2. To determine the relationship between TQM mindset of the nursing personnel and their age, civil status, educational attainment, position length of service, and attendance of TQM seminars.2. To assess the quality of service of the hospital, in general, and the Division of Nursing Pastoral Care, in particular, as perceived by the nursing personnel, other hospital personnel, and patients.3. To determine the relationship between the TQM mindset of nursing personnel and the perceived quality of service of the hospital, in general, and of the Division of Nursing Pastoral Care, in particular.It is hoped that findings of the study will improve TQM implementation in SLH and other health care institutions.